2015
DOI: 10.1530/edm-15-0005
|View full text |Cite
|
Sign up to set email alerts
|

Management of adrenocortical insufficiency with continuous subcutaneous hydrocortisone infusion: long-term experience in three patients

Abstract: SummaryTo assess continuous subcutaneous hydrocortisone infusion (CSHI) in patients with adrenocortical insufficiency (AI) and difficulties with oral replacement. Three patients with AI and frequent hospital admissions attributed to adrenal crises were treated with CSHI, which was delivered via a continuous subcutaneous infusion. All three patients preferred CSHI and remained on it long term, which permitted prolonged follow-up analysis. All three patients reported symptomatic improvement, and in two cases, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In our case, sleeplessness could be related to higher levels of cortisol in the evening, due to the assumption of two doses of hydrocortisone close to bedtime, when maximal glucocorticoid sensitivity of peripheral tissues is reported [ 4 , 6 ]. The observed metabolic impairments during Ramadan practice highlight the need of an individualized therapeutic management plan; intramuscular hydrocortisone [ 7 ], subcutaneous glucocorticoids pumps [ 8 ], and use of long acting steroids such as dexamethasone and prednisone instead of hydrocortisone [ 6 ] could be considered as therapeutic options to adhere Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, sleeplessness could be related to higher levels of cortisol in the evening, due to the assumption of two doses of hydrocortisone close to bedtime, when maximal glucocorticoid sensitivity of peripheral tissues is reported [ 4 , 6 ]. The observed metabolic impairments during Ramadan practice highlight the need of an individualized therapeutic management plan; intramuscular hydrocortisone [ 7 ], subcutaneous glucocorticoids pumps [ 8 ], and use of long acting steroids such as dexamethasone and prednisone instead of hydrocortisone [ 6 ] could be considered as therapeutic options to adhere Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of three AI patients found that with high adherence due to continuous subcutaneous hydrocortisone infusion, patients reported symptom improvement and two of the three cases had reduced hospital admission rates. The decrease in hospital admissions and resulting reduction in inpatient length of stay, reduced treatment costs in comparison with the year prior to continuous infusion [ 16 ]. Adherence is commonly linked to reduced cost of treatment, and alternatively, poor adherence has been cited by the World Health Organization as a driver of health care cost worldwide [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CSHI requires patient training and engagement, necessitating education on pump use and maintenance. There is also a risk of local site infections and dislodgement with interruption of steroid delivery ( 36 ). The subjective health benefits of CSHI have not been conserved between studies and cardiovascular risk as assessed by anthropometric and biochemical markers, has not been adequately explored.…”
Section: Bridging the Mortality Gapmentioning
confidence: 99%
“…However, in a double-blind, placebo-controlled randomised crossover trial comparing oral hydrocortisone and CSHI, there was no additional benefit seen with CSHI in subjective health scores 35 . The use of CSHI is a significant burden on the patient, who will need to be educated on the management of a pump and there is also a risk of local site infections and dislodgement with interruption of steroid delivery 36 . The subjective health benefits of CSHI have not been conserved between studies and cardiovascular risk as assessed by anthropometric and biochemical markers, have not been adequately explored.…”
Section: Bridging the Mortality Gapmentioning
confidence: 99%